Leadership roles of principles in facilitating academic management in secondary schools of Khyber Pakhtunkhwa of Pakistan - Ahmad, Ijaz
This study explores the leadership roles of principals in facilitating academic management in secondary schools of Khyber Pakhtunkhwa province of Pakistan. A qualitative research method was used in this study. Data were collected using a semi-structured interview with six participants, including three principals and three teachers in the Khyber Pakhtunkhwa (KPK) province of Pakistan. Thematic data analysis was used to gather meaningful information, and the researcher used the purposive sampling technique in order to select the sample of the study. In the literature, the leadership quality of a principal in an educational institution has been defined in various ways. However, stakeholders in the education sector in Pakistan's Khyber Pakhtunkhwa province believe that the quality of education should be determined by a broad definition of education that includes the holistic development of learners' personalities rather than the sole indicator of academic achievement. The study discovered that the role of Principals in KPK secondary schools is of paramount importance to any academic field. In KPK, the significance is enormous, but the qualities of leadership lack significantly. The facilities are not up to speed, including shortage of limited resources, infrastructure, training, traditional methods of teaching and evaluation teaching aids are all lacking in abundance. Due to lack of unawareness of education and lack of experience, parents cannot guide their children. It was determined that political objectives and local politicians are interfering with the education system, leading to the authority of school administrators. According to the study's findings, the education system should be decentralized, and school principals should be given greater freedom to manage academic activities and provide effective leadership. It is recommended that the government ensure the principal academic outcomes are improved by ensuring that they have access to the essential educational resources and opportunities. It is recommended that the government introduce a reward system set to motivate teachers' performance, attract and retain students with the knowledge, skills, and abilities required to achieve the reform objectives. As a result, it is also recommended that the education sector be protected from political interference that could harm the overall education system. Training sessions for teachers and principals must be provided continuously to improve the performance of school administrations.